Effects of Animal Manure, Sewage Sludge, and Cadmium Chloride on Cadmium Uptake of Corn Shoots - Masume Sharifi; Majid Afyuni; Amir Hossein Khoshgoftarmanesh (آب و فاضلاب, 2011)
Reusing organic wastes such as sewage sludge is a good way of returning organic matter and nutrients into soil. However, the likelihood of heavy metal accumulation in soil and the subsequent contamination of human and animal food chains should be determined before any attempt is made to reuse organic wastes. The purpose of this greenhouse study was to investigate the impact of sewage sludge from the effluent of Isfahan Polyacryl Corp. on yield and shoot cadmium concentrations in corn as compared to the animal manure and mineral salt of cadmium. A completely randomized design with three treatments (cow manure, sewage sludge at 25 Mg/ha, and 5 and 10 mg/kg Cd as CdCl2) was used. Corn seedlings were harvested 60 days after planting and Cd concentration was measured in the shoot. Application of animal manure and sewage sludge significantly increased corn biomass. Cadmium increment, in both organic and mineral salt treatments, significantly increased cadmium concentration in the corn shoot. The plant cadmium concentration in the soil treated with industrial sewage sludge and CdCl2 were significantly higher than that treated with animal manure.